Electropolymerizable IrIII Complexes with β‐Ketoiminate Ancillary Ligands. Issue 17 (13th August 2019) - Ionescu, Andreea; Caligiuri, Rossella; Godbert, Nicolas; Candreva, Angela; La Deda, Massimo; Furia, Emilia; Ghedini, Mauro; Aiello, Iolinda
Abstract: A series of electropolymerizable cyclometallated Ir III complexes were synthesized and their electrochemical and photophysical properties studied. The triphenylamine electropolymerizable fragment was introduced by using triphenylamine‐2‐phenylpyridine and, respectively, triphenylamine‐benzothiazole as cyclometalated ligands. The coordination sphere was completed by two differently substituted β‐ketoiminate ligands deriving from the condensation of acetylacetone or hexafluoroacetylacetone with para ‐bromoaniline. The influence of the ‐CH3 /‐CF3 substitution to the electrochemical and photophysical properties was investigated. Both complexes with CH3 substituted β‐ketoiminate were emissive in solution and in solid state. Highly stable films were electrodeposited onto ITO coated glass substrates. Their emission was quenched by electron trapping within the polymeric network as proven by electrochemical studies. The ‐CF3 substitution of the β‐ketoiminate leads instead to the quenching of the emission and inhibits electropolymerization. Abstract : Movies on a diet : Thin films of triphenylamine (TPA)‐containing Ir III cyclometalated complexes were obtained by electrodeposition. Electron trapping onto polymerized films was observed.